Specific Radiological Findings of Traumatic Gastrointestinal Tract Injuries in Patients with Blunt Chest and Abdominal Trauma. Issue 2 (May 2015) - Kokabi, Nima; Harmouche, Elie; Xing, Minzhi; Shuaib, Waqas; Mittal, Pardeep K.; Wilson, Kenneth; Johnson, Jamlik-Omari; Nicolaou, Savvas; Khosa, Faisal
Gastrointestinal hollow viscus injury after blunt chest and abdominal trauma is uncommon and complicates 0.6%-1.2% of all cases of trauma. Early recognition of such injuries significantly decreases morbidity and mortality. Since physical examination is not accurate in detecting such injuries, contrast-enhanced computed tomography has been the mainstay for diagnosis in many emergency departments. This pictorial essay aims to review the incidence, mechanisms, and signs of gastrointestinal hollow viscus injuries in the setting of blunt chest and abdominal trauma.